Preoperative hematocrit and platelet count are associated with blood loss during spinal fusion for children with neuromuscular scoliosis. Issue 4 (April 2022) - Lewen, Margaret O; Berry, Jay; Johnson, Connor; Grace, Rachael; Glader, Laurie; Crofton, Charis; Leahy, Izabela; Pallikonda, Nikhil; Litvinova, Anna; Staffa, Steven J; Glotzbecker, Michael; Emans, John; et al.
Aim: To assess the relationship of preoperative hematology laboratory results with intraoperative estimated blood loss and transfusion volumes during posterior spinal fusion for pediatric neuromuscular scoliosis. Methods: Retrospective chart review of 179 children with neuromuscular scoliosis undergoing spinal fusion at a tertiary children's hospital between 2012 and 2017. The main outcome measure was estimated blood loss. Secondary outcomes were volumes of packed red blood cells, fresh frozen plasma, and platelets transfused intraoperatively. Independent variables were preoperative blood counts, coagulation studies, and demographic and surgical characteristics. Relationships between estimated blood loss, transfusion volumes, and independent variables were assessed using bivariable analyses. Classification and Regression Trees were used to identify variables most strongly correlated with outcomes. Results: In bivariable analyses, increased estimated blood loss was significantly associated with higher preoperative hematocrit and lower preoperative platelet count but not with abnormal coagulation studies. Preoperative laboratory results were not associated with intraoperative transfusion volumes. In Classification and Regression Trees analysis, binary splits associated with the largest increase in estimated blood loss were hematocrit ≥44% vs. <44% and platelets ≥308 vs. <308 × 10 9 /L. Conclusions: Preoperative blood counts may identify patients at risk of increased bleeding, though do not predict intraoperative transfusion requirements. Abnormal coagulation studies often prompted preoperative intervention but were not associated with increased intraoperative bleeding or transfusion needs.